Best vitelliform macular dystrophy in a Swedish family: genetic analysis and a seven‐year follow‐up of photodynamic treatment of a young boy with choroidal neovascularization. (26th April 2013) - Frennesson, Christina I.; Wadelius, Claes; Nilsson, Sven Erik G.
Abstract. Purpose: To determine the mutation in a Swedish family with Best disease (vitelliform macular dystrophy; VMD) and to investigate the short‐ and long‐term effects of photodynamic treatment (PDT) on subretinal neovascularization in a young boy. Methods: The five members of three generations of a family with VMD underwent a thorough ophthalmological examination, including best‐corrected visual acuity (VA), visual field, colour vision, biomicroscopy of the posterior segment (dilated), fundus photography and electro‐oculography (EOG). For the proband, an eleven‐year‐old boy, his father and grandfather, dark adaptation test, angiography and electroretinography (ERG) were also performed. After PCR amplification, the genotype was determined by cleavage with restriction enzyme, specific for the W93C allele. Results: Four family members had an abnormal EOG response. All showed the W93C mutation in the VMD2 gene. Visual acuity ranged from 20/20 to 20/250. The fundus manifestations varied from minor pigmentary changes over egg yolk‐like lesions to chorioretinal atrophy, and fluorescein angiography showed corresponding pathology. In the proband, VA decreased during follow‐up from 0.5 (20/40) to 0.08 (20/250) due to a subfoveal neovascularization with haemorrhage, and PDT with visudyne was begun. The haemorrhage resolved within 2 months, and after three treatments, VA had increased to 0.25 (20/80). One year later, acuity had improved to 0.5 (20/40), and this result was stable throughout the 7 years of the follow‐up. Conclusion: The mutation was determined to be W93C, the most common mutation in VMD in Sweden. In an eleven‐year‐old boy with subretinal neovascularization, PDT seemed to be beneficial also in a long‐term follow‐up.